Peran Nutrisi Seimbang dalam Optimalisasi Sistem Endokrin untuk Menjaga Homeostasis dan Mencegah Penyakit Kronis - Angella Putri Ramadhani; Az-zhara Diah Putri Nugroho; Chika Muthi’atul Fadhilah; Suci Rahmawati; Vania Nabila Arisanti; Wulan Indriani; Liss Dyah Dewi Arini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The endocrine system plays a crucial role in maintaining the stability of the body's physiological functions through the regulation of hormones, which operate in a complex and interconnected manner. Imbalances in this system, which can be caused by unhealthy lifestyle and dietary factors, are a major trigger for chronic diseases such as type 2 diabetes mellitus, thyroid disorders, and metabolic syndrome. This study aims to examine how a balanced nutritional pattern—both macronutrients (complex carbohydrates, high-quality proteins, and healthy fats) and micronutrients (vitamins and minerals)—supports optimal endocrine system function. A literature review revealed that excesses or deficiencies of certain nutrients can affect hormone production, metabolism, and effectiveness. For example, magnesium deficiency can inhibit insulin sensitivity, while iodine deficiency affects thyroid gland function. Therefore, adopting a balanced and nutritious diet is not only crucial for maintaining homeostasis but also plays a role in preventing endocrine disorders and sustainably reducing the risk of chronic diseases